Effect of nitrogen, phosphorus and flower stage of development on carotenoids and oil content of marigold (Tagetes patula L.) - Ali Aburigal, Yasmin (Gezira Journal of Agricultural Science; Vol 9 No 2 (2011), 2011)
Seeds of marigold collected from local ornamental plants were grown at the farm of the Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan, during the 4 th of March, 2007. The objective of the study was to investigate the effect of N, P and flower stage of development on carotenoids and oil contents of marigold ( Tagetes patula L.). The study consisted of three rates of N (0, 43 and 86 kgha -1 ) and two P levels (0, 41 kg P 2 O 5 ha -1 ). Flowers were harvested at the unopened, newly opened, mature and over mature stages. Treatments were arranged in a randomized complete block design with three replicates. Nitrogen and phosphorus fertilizers significantly increased plant height and number of branches of marigold. However, they did not affect flower carotenoids content. Marigold flowers contained about 5 different carotenoids including lutein, the major component and β-carotene. When compared with salad rocket which is a lutein rich plant, most of the lutein of marigold flowers was present in the esterified form in contrast to rocket leaves, in which case lutein was largely in the free form. Five carotenoids types appeared in marigold flowers 15 days after flower opening and less types were observed in younger and older flowers. The seeds of marigold contained 1.5% of fixed oil, the major fatty acid of which was linoleic acid.    تمت زراعة بذور الماريقولد التي جمعت من نباتات زينة محلية  في مزرعة  كلية العلوم الزراعية، جامعة الجزيرة، وادمدني، السودان, في الرابع من مارس, 2007. الهدف من الدراسة هو بحث تاثير سماد النيتروجين والفسفور ومراحل نمو الزهرة على صبغة الكاروتين ومحتوى الزيت في زهرة الماريقولد ( Tagetes patula L.)   كانت مستويات النيتروجين صفر، 43، 86 كجم نيتروجين/هكتار ومستويات سماد الفسفور صفر, 41 كجم P 2 O 5 /هكتار. حصدت الازهار في مراحل نمو مختلفة وهي: قبل ان تتفتح، ومباشرة بعد تفتح الزهرة ومكتملة النضج وبعد 15 يوما من التفتح. تم استخدام تصميم القطاعات العشوائية الكاملة. أوضحت نتائج التجربة  أن المعاملة بالنيتروجين والفسفور أدت الى زيادة معنوية في طول النبات وعدد الافرع في نبات الماريقولد، ولكنها لم تؤثر على محتوى الكاروتينات الموجودة في أزهار الماريقولد كما أوضحت طريقة كروماتوغرافيا الطبقة الرقيقة أن أزهار الماريقولد تحتوي على حوالي 5 أنواع مختلفة من الكاروتينات بما فيها ليوتين وبيتاكاروتين. الليوتين الموجود في الماريقولد يوجد بصورة مرتبطة في شكل إستر مقارنة بالليوتين الموجود في الجرجير والتي يوجد فيها الليوتين بصورة حرة. ظهرت 5 أنواع من الكاروتينات في زهرة الماريقولد بعد 15 يوم من تفتح الأزهار، ووجدت نسبة أقل في الأزهار الأقل والأكبر عمراً. تحتوي بذور الماريقولد على1.5% من الزيوت الثابتة  والمكون الأساسي لها من الأحماض الدهنية هو حمض اللينوليك.